The Opportunities and Critical Challenges of Middle Education Curriculum Implementation in Primary Schools: A Case Study of Wolaita Zone, Ethiopia - Gizachew, Mandado; Areaya, Solomon (IJER (Indonesian Journal of Educational Research), 2024)
The purpose of this study is to examine the opportunities and critical challenges of curriculum implementation in middle education in case schools. The study adopted a qualitative case study research approach and purposely selected four teachers, representatives of students, and parents, and in the case of availability, principals participated in collecting primary data through interviews and FGD. Document reviews and observations were also conducted to collect the data. Data were analyzed by narrating and categorizing each theme, and finally triangulating the findings of the study based on the objectives of the study. The findings of the study imply opportunities, critical challenges, and directions for further improvement of the curriculum in case schools. According to the major findings of the study, there were some good opportunities in case schools, such as students and teachers with similar backgrounds in the case of first language or cultural aspects, existence teachers, and school principals according to the standard of qualification status of middle education and the availability of basic school facilities, even if there were utilization issues. The study has also shown critical challenges, such as the attitude and practice of stakeholders in the case of curriculum implementation, shortage of textbooks and training based on curriculum reform, and context-related variables. Finally, cooperation and collaboration among stakeholders are suggested to improve the practice of curriculum implementation..